2007
DOI: 10.1080/00343400600928285
|View full text |Cite
|
Sign up to set email alerts
|

Recasting the Creative Class to Examine Growth Processes in Rural and Urban Counties

Abstract: McGranahan D. and Wojan T. (2007) Recasting the creative class to examine growth processes in rural and urban counties, Regional Studies 41, 1-20. Richard Florida's Rise of the Creative Class (2002) makes a compelling argument that regional development now depends on novel combinations of knowledge and ideas, that certain occupations specialize in this task, that people in these occupations are drawn to areas providing a high quality of life, and thus the essential development strategy is to create an environm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
295
0
14

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 372 publications
(323 citation statements)
references
References 11 publications
14
295
0
14
Order By: Relevance
“…In contrast, late studies (i.e. McGranahan and Wojan, 2007;Gülümser et al, 2009) showed that the increase of creative class does not depend on the physical distance or R&D, but depends on the attractiveness capacity of rural regions and the motivation of entrepreneurs. Thus, there is no single sign of the association between physical distance and rural creative capacity but the reduction of the physical distance which can be obtained by the increase of the accessibility and different mode of transportation and also by the decrease of travel time and cost can be measured by the increase of individuals reaching the rural regions with their own abilities.…”
Section: Measuring Creative Capacity Of Rural Regionsmentioning
confidence: 92%
See 1 more Smart Citation
“…In contrast, late studies (i.e. McGranahan and Wojan, 2007;Gülümser et al, 2009) showed that the increase of creative class does not depend on the physical distance or R&D, but depends on the attractiveness capacity of rural regions and the motivation of entrepreneurs. Thus, there is no single sign of the association between physical distance and rural creative capacity but the reduction of the physical distance which can be obtained by the increase of the accessibility and different mode of transportation and also by the decrease of travel time and cost can be measured by the increase of individuals reaching the rural regions with their own abilities.…”
Section: Measuring Creative Capacity Of Rural Regionsmentioning
confidence: 92%
“…In contrast, rural regions have become subject to creative capacity studies in the last few years. These late applications showed that rural creative capacity calls for a rural specific approach as urban specific creativity theories and methods misrepresent/underestimate the creative capacity of rural regions (McGranahan and Wojan, 2007).…”
Section: Creative Capacity In the Field Of Regional Sciencementioning
confidence: 99%
“…McGranahan and Wojan (2007) concentrate on rural counties in the United States and find support for Florida's creative class thesis. Donegan and Lowe (2008) contend that cities with a large creative talent pool are also more likely to have substantial income inequality.…”
Section: Overview Of the Issues And The Literaturementioning
confidence: 94%
“…Such firms represent a powerful medium for inducing and encouraging the creation of new businesses and jobs; are a promising source of wealth for society; and form an important element of a vital urban or regional economy (see e.g., Florida, 2002Florida, , 2004Lee et al, 2004;McGranahan and Timothy, 2007).…”
Section: Innovative Firms As Complex Carriers Of a Creative Economymentioning
confidence: 99%